Delays in referral from primary care are associated with a worse survival in patients with esophagogastric cancer. Issue 10 (1st March 2019) - Arhi, Chanpreet S; Markar, S; Burns, E M; Bouras, G; Bottle, A; Hanna, G; Aylin, P; Ziprin, P; Darzi, A
SUMMARY: NICE referral guidelines for suspected cancer were introduced to improve prognosis by reducing referral delays. However, over 20% of patients with esophagogastric cancer experience three or more consultations before referral. In this retrospective cohort study, we hypothesize that such a delay is associated with a worse survival compared with patients referred earlier. By utilizing Clinical Practice Research Datalink, a national primary care linked database, the first presentation, referral date, a number of consultations before referral and stage for esophagogastric cancer patients were determined. The risk of a referral after one or two consultations compared with three or more consultations was calculated for age and the presence of symptom fulfilling the NICE criteria. The risk of death according to the number of consultations before referral was determined, while accounting for stage and surgical management. 1307 patients were included. Patients referred after one (HR 0.80 95% CI 0.68–0.93 p = 0.005) or two consultations (HR 0.81 95% CI 0.67–0.98 p = 0.034) demonstrated significantly improved prognosis compared with those referred later. The risk of death was also lower for patients who underwent a resection, were younger or had an earlier stage at diagnosis. Those presenting with a symptom fulfilling the NICE criteria (OR 0.27 95% CI 0.21–0.35 p < 0.0001) were more likely to be referred earlier. This is the first study to demonstrate an association between a delay in referral and worse prognosis in esophagogastric patients. These findings should prompt further research to reduce primary care delays.